2021
DOI: 10.1177/1357633x211053738
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of telehealth versus face-to face interventions for anxiety disorders: A systematic review and meta-analysis

Abstract: Introduction Worldwide, it is estimated that 264 million people meet the diagnostic criteria for anxiety conditions. Effective treatment regimens consist of cognitive and behavioural therapies. During the COVID-19 pandemic, treatment delivery relied heavily on telemedicine technologies which enabled remote consultation with patients via phone or video platforms. We aim to identify, appraise and synthesise randomised controlled trials comparing telehealth to face-to-face delivery of care to individuals of any a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 32 publications
3
32
0
Order By: Relevance
“…For common mental health conditions, there is evidence that telehealth is an effective modality in the provision of psychological therapy as face-to-face therapy. There is some evidence of equivalence between videoconferencing and face-to-face care for depression [ 20 ], anxiety [ 21 , 22 ], PTSD [ 23 ], and psychotherapy broadly [ 5 ]. Furthermore, there is evidence of telephone-delivered therapy being effective for depression and anxiety [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For common mental health conditions, there is evidence that telehealth is an effective modality in the provision of psychological therapy as face-to-face therapy. There is some evidence of equivalence between videoconferencing and face-to-face care for depression [ 20 ], anxiety [ 21 , 22 ], PTSD [ 23 ], and psychotherapy broadly [ 5 ]. Furthermore, there is evidence of telephone-delivered therapy being effective for depression and anxiety [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…We included studies with people of any age or gender, who were receiving psychotherapy for less common mental health conditions, such as bulimia nervosa and substance use disorder, or any conditions where psychotherapy was used, such as cognitive behavioral therapy (CBT) for patients with cancer with high psychological needs. Although anxiety [ 22 ], depression (Scott AM et al, PhD, unpublished data, February 2022), and PTSD [ 23 ] were within the scope of this review, there was enough literature to conduct separate systematic reviews by condition, and hence, these were excluded. Studies involving hospital patients (eg, explicitly identified as taking place in hospital wards, or with patients shortly after discharge) or those consulting a secondary or tertiary specialist (ie, a psychiatrist) were excluded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Digitally delivered mental health services that leverage videoconferencing technology have emerged as a scalable option to meet this demand [ 7 ]. Technology-enabled mental health care that delivers virtual one-on-one support appears to produce similar outcomes as in-person treatment [ 8 , 9 ] and offers several promising solutions to enhance care. Digital platforms that collect information before treatment can use patient characteristics and preferences to identify and deliver the most effective yet least burdensome and least costly intervention from a range of care modalities, including psychotherapy with paraprofessionals or licensed therapists [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The types of mental health services offered through digital means are comprehensive, with most one-on-one care shifting to videoconferencing meetings or phone calls. Although telehealth services produce similar outcomes to in-person treatment (Krzyzaniak et al, 2021 ; Thomas et al, 2021 ), questions remain about whether a virtual setting is conducive to the development and maintenance of a strong therapeutic alliance between patients and providers (Simpson & Reid, 2014 ).…”
Section: Introductionmentioning
confidence: 99%